2014
DOI: 10.1111/efp.12149
|View full text |Cite
|
Sign up to set email alerts
|

Detection of living Bursaphelenchus xylophilus in wood, using reverse transcriptase loop‐mediated isothermal amplification (RT‐LAMP)

Abstract: Pinewood nematode (PWN), Bursaphelenchus xylophilus, the causal agent of pine wilt disease, is an inhabitant of native pine species of North America, where its presence has minor impact. In contrast, the introduction of this nematode to forests in Asia and Europe has devastated some pine stands and is recognized as a pest of significant phytosanitary concern by the National Plant Protection Organizations of several countries. The ability to detect PWN in internationally traded wood products is crucial to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Only three samples had high C T values indicating PCR inhibition.Increased co-extraction of PCR inhibitors such as phenolic compounds(Langrell & Barbara, 2001;Leal et al, 2015;Lee & Cooper, 1995;Schneider et al, 2009) may occur in certain samples depending on various factors, such as infection stage, host and environmental conditions, and additional purification steps would be necessary to obtain reliable qPCR results in such cases.4.2 | Detection of Dothistroma septosporum, Dothistroma pini and Lecanosticta acicolaAmong all infected trees, D. septosporum was the most prevalent pathogen. In the present study, 97% of the samples extracted with the KingFisher TM Flex Purification 96System resulted in optimal amplification of the internal qPCR control.…”
mentioning
confidence: 99%
“…Only three samples had high C T values indicating PCR inhibition.Increased co-extraction of PCR inhibitors such as phenolic compounds(Langrell & Barbara, 2001;Leal et al, 2015;Lee & Cooper, 1995;Schneider et al, 2009) may occur in certain samples depending on various factors, such as infection stage, host and environmental conditions, and additional purification steps would be necessary to obtain reliable qPCR results in such cases.4.2 | Detection of Dothistroma septosporum, Dothistroma pini and Lecanosticta acicolaAmong all infected trees, D. septosporum was the most prevalent pathogen. In the present study, 97% of the samples extracted with the KingFisher TM Flex Purification 96System resulted in optimal amplification of the internal qPCR control.…”
mentioning
confidence: 99%
“…First, PCR and quantitative real-time PCR based PWN detection methods were not suitable for on-site diagnosis since these methods require expensive experimental devices such as PCR machine and electrophoresis devices. When four primers are used, however, the amplification time required for detection of the result takes more than an hour (Kang et al, 2015;Kikuchi et al, 2009;Leal et al, 2015). While this method is useful in labs with stable power supplies, it is difficult to use where power supplies are not stable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the experimental time required to confirm the detection result is more than an hour (Cardoso et al, 2012;Francois et al, 2007;Hu et al, 2011;Kang et al, 2004;Takeuchi et al, 2005). Furthermore, recent studies about PWN detection using the LAMP method argue that it is an improvement over PCR based approaches (Kikuchi et al, 2009;Leal et al, 2015). Second, in the LAMP method, four to six primers are used to synthesize target DNA amplicons.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA extraction from 2-2.5 g of pellet wood samples, the authors modified the method by Chomczynski & Sacchi (1987) as reported in Leal et al (2015) to improve extraction quality from woody tissue. In order to extract the DNA from the same sample, 7.5 mL of ethanol was added to the phenol phase saved from the RNA extraction.…”
Section: Pinewood Nematode Total Rna and Dna Extractionmentioning
confidence: 99%
“…A positive extraction control was used to ensure that the protocol for RNA extraction from wood was successful in producing amplifiable RNA/cDNA. In this control, RNA was extracted, prior to cDNA synthesis and PCR, from wood free from pinewood nematodes spiked with approximately 1000 nematodes (Leal et al, 2015).…”
Section: Pinewood Nematode Cdna Synthesismentioning
confidence: 99%